Three Keys to Retaining Talented Teachers in the UAE: Leadership, Community, and Work-Life Balance - A Phenomenological Case Study in the Emirate of Ras Al Khaimah - Troy N. Herrera; Alexandria Proff (Athens Institute for Education and Research, 2023)
The United Arab Emirates hires many teachers from abroad to work in both the private and public school systems. Recruiting foreign teachers can be exceedingly costly, especially when one considers the financial investment associate with air fare, health insurance, housing, transportation, and a competitive salary, along with the substantial processing time involved in issuing work visas, professional and intercultural training. One way organizations may be able to save on additional expenditures is to retain the teachers who have been hired and are already settled in the country. Naturally, a substantial part of the decision for the teacher to remain working and living in the UAE lies with the expatriate teacher. This exploratory, case study employed a qualitative approach in which descriptive data was collected from six in-depth, semi-structured interviews exploring job satisfaction as one, of what may be other, indicators associated with of length-of-stay among expatriate teachers in the UAE. These descriptive data were analyzed using an interpretive analysis, which culminated with three selective codes: (1) Leadership and community are key to expatriate teacher's job satisfaction; (2) School leaders' engagement in improving behavior management would improve satisfaction; and (3) Positive work-life balance may influence expatriate teachers' length of stay in the UAE. Taken collectively, this data may assist decision-makers, school leaders, and policy-makers on how to foster environments that promote retention among expatriate teachers in the UAE.